Molecular characterization and association studies of CYP19 (aromatase) allelic variants with reproduction and production traits in Sahiwal and Hariana cattle - UTTAM, VISHAKHA; TIWARI, MADHU; SINGH, SATYENDRA PAL; SHARMA, DEEPAK; KUMAR, AVNEESH; KUMAR, ADITYA (The Indian Journal of Animal Sciences, 2022)
Anestrus is a major reproductive problem in bovines which occurs due to less secretion of estrogen from the ovarian follicles. Enzyme cytochrome P450 aromatase which helps in estrogen biosynthesis is encoded by CYP19 gene. In the current study, characterization of exon 9 and 10 region and polymorphic study in 5’ UTR region of CYP19 gene was undertaken in Indian Sahiwal and Hariana cattle. Studied Indian cattle breeds showed 100% homology to Nelore and crossbred cattle, and 99.8% to Bos taurus at nucleotide level while at amino acid level, they showed 100% homology to Nelore and crossbred cattle, and 99.4% to Bos taurus. CYP19/PvuII PCR-RFLP assay conducted in 100 Sahiwal and 100 Hariana cattle revealed three types of genotype namely AA (405 bp), AB (405 bp, 327 bp and 78 bp) and BB (327 bp and 78 bp). The AA genotype was more frequent (58.5%) followed by AB (37.0%) and BB (4.5%) genotypes and Chi square analysis revealed the populations was in Hardy-Weinberg equilibrium. The allelic frequency of A and B allele was observed as 0.77 and 0.23, respectively. Association study of CYP19/PvuII genotypes with reproduction and production traits revealed no significant difference.